Contemporary Wedding in Indonesia (Study of Mubarakah Wedding at Hidayatullah Islamic Boarding School, Balikpapan, East Kalimantan) - Abdullah; Hijrah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research aims to examine in depth a new concept of marriage which was initiated by the manager of the Hidayatullah Islamic Boarding School behind the board, this concept according to the experts can be an alternative solution in building a harmonious family as the first step in building a peaceful and prosperous world civilization. This research is an empirical legal research, in collecting data, this research uses interview, observation and documentation methods. This research found that the Hidayatullah Balik Papan Islamic Boarding School designed the concept of marriage which is relatively new, there are no classical or contemporary fiqh studies that discuss about it. this concept is termed as Mubarakah Marriage, the Mubarakah marriage process is divided into three, they are Pre-Marriage, Marriage Process and Post-Marriage. The process includes First, mubarakah marriage participants are required to follow the pre-wedding briefing quarantine, Second marriage is carried out without dating or ta'aruf, the three partners are chosen by the committee, marriage participants will know their match for sure after the contract, the four contract processes and receptions are carried out bulkly and it is free of charge, fifth post-wedding Family guidance. The principles of this marriage are religiosity, cheap, easy and simple, pre-marriage guidance to post-marriage, and the principle of da'wah. The effectiveness of this concept in family resilience is very high because 92% of married couples remain intact until now.